2011
DOI: 10.3233/cbm-2010-0186
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of urinary proepithelin as a potential biomarker for bladder cancer detection and prognosis in Egyptian patients

Abstract: This preliminary study suggests that urinary proepithelin may be considered as a non-invasive, sensitive, and specific urine-based test for bladder cancer diagnosis and/or prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Also, there is a positive correlation between urinary progranulin mRNA and protein. This is in agreement with the study of (Selmy et al, 2010) who found that progranulin levels in voided urine samples from bladder cancer patients was significantly higher in patients with malignant lesions compared to healthy individuals (Selmy et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, there is a positive correlation between urinary progranulin mRNA and protein. This is in agreement with the study of (Selmy et al, 2010) who found that progranulin levels in voided urine samples from bladder cancer patients was significantly higher in patients with malignant lesions compared to healthy individuals (Selmy et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…This is same specificity but a higher sensitivity result than the study of (Selmy et al, 2010) that revealed that measuring urinary progranulin level test has a test sensitivity and specificity to detect the presence of bladder cancer as 74.6 and 85.2%, respectively. Both studies are just preliminary studies that needed further researches to fully test effectiveness of measuring progranulin urinary level as a sensitive and specific test for cancer bladder.…”
Section: Discussionmentioning
confidence: 62%
“…PGRN mRNA expression levels was higher in high-grade bladder cancer than that of low-grade bladder cancer, and overexpression of PGRN were observed in patients who died after 5 years of follow-up compared with those alive after 5 years of follow-up treatment [41,42]. PGRN levels in voided urine samples from bladder cancer patients revealed that PGRN level was significantly higher in patients with malignant lesions compared to healthy individuals [43].…”
Section: Ovarian Cancermentioning
confidence: 89%
“…Also, in the same study, tissue samples from patients with renal cell carcinoma show higher levels of PGRN expression compared with low-grade renal cell carcinoma and normal tissue [84]. In patients with bladder cancer, urinary levels of PGRN are significantly increased relative to control samples; in addition, high PGRN levels correlate with the stage and pathological cancer grade [85]. Unfortunately, the small sample size of this study is a limitation; however, the results suggest that urine PGRN levels may serve as a simple test as part of a bladder cancer work-up.…”
Section: Progranulin As Cancer Biomarkermentioning
confidence: 96%